Trends in prescription of new antiseizure medications in a single center in Latin America: evidence of clinical practice - Colado-Martinez, Jimena; Gonzalez-Salido, Jimena; Fuentes-Calvo, Irving; Vázquez-Cruz, Betsy C.; Vasquez-Lopez, Fernando; Robles-Lomelin, Pilar; Solis-Velázquez, Alan M.; Marin-Castañeda, Luis A.; Rivas-Cruz, Mijail A.; Barrios-González, Diego A.; Valenzuela-Mendivil, Eithel; Sotelo-Díaz, Fernando; et al. (Frontiers in Neurology, 2025)
BackgroundEpilepsy affects approximately 70 million people globally, with a prevalence in Mexico of 10.8 to 20 cases per thousand. Antiseizure Medications (ASM) are the first line of treatment for people with epilepsy (PWE), aiming to achieve early seizure control while minimizing adverse effects that could impact quality of life.Materials and methodsThis retrospective cohort study analyzed data from 2020 to 2024 collected from medical records, clinical histories, and electronic systems, using REDCAP® and SPSSV21®. It included all epilepsy patients treated at the National Institute of Neurology and Neurosurgery “MVS” in Mexico City. Descriptive statistics were reported as means ± standard deviations for quantitative variables and percentages for categorical variables. Bivariate analysis used the Q Cochran test for dichotomous variables and the chi-square or Fisher’s exact test for qualitative variables.ResultsOf 1,192 prescriptions, third-generation ASMs accounted for the majority (53.7%), led by levetiracetam (24.1%), lamotrigine (14%), and lacosamide (6%). Second-generation ASMs comprised 42.4%, including valproate (21.5%), carbamazepine (11.3%), and clonazepam (5.5%). First-generation ASMs were less frequently prescribed (3.9%), primarily phenytoin (2.3%), primidone (1.0%), and phenobarbital (0.3%). Third-generation ASMs were the most prescribed for focal seizures (38.6%), generalized seizures (13.3%), and seizures of unknown (1.9%) or unclassified types (2.1%).DiscussionCompared to a 2012 study in the same population, which showed second-generation ASM as dominant, this study highlights a significant shift toward third-generation ASM, now representing over half of prescriptions. While valproate and carbamazepine remain versatile second-generation options, newer ASMs, such as levetiracetam, are increasingly favored.ConclusionThese findings demonstrate a preference for second- and third-generation ASMs in tertiary hospitals in Latin America, which is concordant with global trends. First-generation ASMs are still prescribed but at lower rates. These results provide insights into changing prescription practices and access to newer medications, informing future research and hospital policies.